PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN GENIALLY PADA MATERI OPERASI BENTUK ALJABAR UNTUK KELAS VII DI MTs MUHAMMADIYAH 1 SAMARINDA - Afiatushalihah, Nazifa; Rusdiana, Rusdiana; Untu, Zainuddin; Haryaka, Usfandi (INSPIRAMATIKA, 2025)
This study aims to design mathematics learning media using Genially for algebraic operations material that meets the criteria of validity and practicality. The method applied is Research and Development (R&D) with the adaptation of the ADDIE model. However, only four stages were carried out, namely the Analysis, Design, Development, and Implementation stages. The research instruments used were validation questionnaires for media and material experts and practicality questionnaires for students and teachers. The results of the study showed: (1) The development of mathematics learning media using Genially on algebraic operations material with the ADDI model consists of four stages. The first stage is analysis, which includes analysis related to initial needs and school curriculum. The second stage is design, which is designing a learning media product which is then named MARBEL. The third stage is development, which is carried out by testing the validity of the product through assessments by media and material experts. Finally, the implementation stage, which is carried out by testing the practicality of the product to mathematics teachers and 18 class VII A students at MTs Muhammadiyah 1 Samarinda; (2) The MARBEL learning media is stated as “very valid” with an average score of 85.6%, seen from the validation results score by media experts of 91% and material experts of 82%; (3) The practicality of the MARBEL learning media is stated as “practical” with an average score of 85.6%, seen from the results of practicality by teachers of 86% and students of 87%.